2011
DOI: 10.1007/s00418-011-0796-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface expression of 27C7 by neonatal rat olfactory ensheathing cells in situ and in vitro is independent of axonal contact

Abstract: Olfactory ensheathing cells (OECs) are Schwann cell-like glial cells of the olfactory system that promote neural regeneration after transplantation into the injured central nervous system. Compared to the closely related Schwann cells, however, the biological characterization of OECs has remained fragmentary. This is due to the fact that the expression of OEC-specific markers is subject to complex regulation and that intricate ultrastructural analysis is essential to determine their localization. The p75 neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…Though it is well known that up-regulation of p75 NTR expression in cultured glial cells, e.g. olfactory ensheathing cells, only requires a short time interval of 2-4 days (Bock et al, 2007;Brandes et al, 2011;Wewetzer et al, 2005), NTR expression in cultures from adult canine brain is not detectable until 15 days in dissociation culture (Orlando et al, 2008) or until 10 days in organotypic slices as observed in the present study. Thus, the delayed initiation of p75 NTR expression argues for differentiation of precursor cells rather than for up-regulation of p75 NTR in mature glia.…”
Section: Phenotype and Origin Of Schwann-like Glia From Adult Canine contrasting
confidence: 76%
See 1 more Smart Citation
“…Though it is well known that up-regulation of p75 NTR expression in cultured glial cells, e.g. olfactory ensheathing cells, only requires a short time interval of 2-4 days (Bock et al, 2007;Brandes et al, 2011;Wewetzer et al, 2005), NTR expression in cultures from adult canine brain is not detectable until 15 days in dissociation culture (Orlando et al, 2008) or until 10 days in organotypic slices as observed in the present study. Thus, the delayed initiation of p75 NTR expression argues for differentiation of precursor cells rather than for up-regulation of p75 NTR in mature glia.…”
Section: Phenotype and Origin Of Schwann-like Glia From Adult Canine contrasting
confidence: 76%
“…Organotypic slice cultures were established according to Heimrich and Frotscher (1993) with modifications (Brandes et al, 2011;Omar et al, 2011). Briefly, the isolated olfactory bulb was placed on a plate of low-adhesive plastic (VulcolanÒ) and sections were cut (350 lm) using a tissue chopper (Mc Illwain, Mickle Lab, Engineering Surrey, UK).…”
Section: Organotypic Slice Cultures Of the Adult Canine Olfactory Bulbmentioning
confidence: 99%
“…OECs display a changeable morphological and molecular phenotype (Alexander et al 2002;Vincent et al 2005), therefore, making it difficult to identify them. Brandes et al (2011) showed that the cell surface antigen 27C7, a marker for non-myelinating Schwann cells (Wewetzer et al 1997), is expressed constitutively in neonatal rat OECs and this expression remained stable in cultured OECs. Therefore, the authors regard the 27C7 antigen to be a valuable marker for the identification of OECs in different experimental setups.…”
Section: Central Nervous Systemmentioning
confidence: 98%
“…It is very likely that the entry of a virus into the brain during intranasal immigration happens via this route. Therefore, it is recommended to test potential life virus vaccines in vitro, because the olfactory ensheathing cells can be cultured [37].…”
Section: Structure Of the Nosementioning
confidence: 99%